Assessing the sustainability of direct potable water re-use the Beaufort West Reclamation Plant - Naroth, Nadine (My University, 2016)
A growing population, rapid urbanisation, and climate change are increasing the pressure on water supplies. The chances of finding new freshwater sources for urban areas are becoming nearly impossible, implying that existing water supplies must go further to satisfy the basic need of potable water. Water reclamation involves the treatment of wastewater to meet defined water quality standards so that it may be reused. Direct potable reuse refers to the introduction of wastewater, which has been treated to meet specified standards, directly into the potable water supply distribution system. Water reuse has become an attractive alternative since wastewater is constantly being produced by populations, which can be treated for reuse. This study examines the sustainability of water reclamation for potable purposes, through an assessment of the Beaufort West Water Reclamation Plant, which includes interviews with the plant manager and process controllers, as well as a review of the relevant documentation. The study employs the use of economic, environmental and societal indicators as a tool in determining the sustainability of water reclamation. The results of the research show that direct potable reuse may be a sustainable solution to reducing the stress on water resources, although certain aspects of the reclamation process require further development in order to progress toward sustainability. In order to provide a long term solution, water reclamation will have to be implemented in conjunction with other water conservation strategies.
A Research Report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering University of Witwatersrand Johannesburg, February 2016
Keywords: Water reuse--South Africa--Beaufort West; Water--Recycling--South Africa; Water quality management--South Africa--Beaufort West; Climatic changes--South Africa